Adequacy of Safe City Programme in preventing snatch theft under the Penal Code (revised 1997) in Malaysia: with special reference to the legal position in the United Kingdom / Nurul Shuhada Suhaimi ... [et al.] - Suhaimi, Nurul Shuhada; Lenny, James Matah; Moulton, Noorie Haryaniee (2014)
Criminal activities have become one of the major concerns, not entirely in Malaysia but around the world. The alarming statistic of criminal cases, particularly snatches theft has been extensively reported in the media, both conventional and social due to its impact towards the victims, their families and the society. The earnestness of the crime have led governments in many states to implement Safe City Program especially in urban arenas. This plan has been put in as one of the steps in bringing down the crime rate as it aims at creating a safe and peaceful surroundings of the urban center and housing as well as to uphold the security of the community. This concept paper exploits the literature review in examining the sufficiency of the Safe City Program in preventing snatch theft under the Penal Code (Revised 1997) in Malaysia. Since the implementation of Safe City Programme in Malaysia still at the initial stage and is progressing, it is apparent that the question of adequacy of Safe City Program in preventing snatch theft under the Penal Code (Revised 1997) in Malaysia can only be effectively addressed by carefully examining the strengths and weaknesses of the current legislation with special reference to the legal position in the United Kingdom in order to identify the gaps that need to be filled.